Secondary degenerative changes in the intervertebral disc due to zygapophyseal (para-vertebral) facet joint lesions. - Boshoff, Willem Hendrik (My University, 2007)
This study design was built around investigating the correlation between facet joint degeneration and ipsilateral annular fissuring or degeneration of the intervertebral disc. It was necessary to establish firstly whether this combination existed and if so, how prevalent it was. The study design incorporates macroscopic and microscopic examination of the intervertebral disc as well as the injection of a radio opaque dye into the nucleus in order to observe dye migration and identify fissuring in the anulus fibrosus of the intervertebral disc. The articulating facet joints were also examined macroscopically and microscopically. A correlation of findings reported in a tabular form should then reveal the existence of the foregoing proposition. The dissertation design did not incorporate examination of range of motion, but the effect of motion was reported in the literature review.
Student Number : 9707737A - MSc Dissertation - School of Anatomical Sciences - Faculty of Health Sciences
Keywords: vertebral; facet; joint; lesions